Gastropleural fistula due thoracoabdominal trauma by the firearms projectile, report of a case: Fístula gastropleural por trauma toracoabdominal por proyectil de arma de fuego, reporte de caso - Cotera Abad, Gabriela Tula (2018)
ABSTRACT The gastropleural fistula is an unusual pathological condition that requires a high index of diagnostic suspicion. A 30-year-old male patient was admitted to the María Auxiliadora Hospital due to a thoracoabdominal trauma opened by a firearm projectile, with an entrance hole in the left anterior hemithorax at the level of the 6th intercostal space and exit orifice in the right posterior hemithorax at the D10 level. When a hemopneumothorax was suspected, a thoracic drainage tube was placed and an exploratory laparotomy was performed after suspicion of gastric perforation. On the ninth day, 400cc of smelly greenish-green discharge with food debris in a thoracic drainage bottle was evident. The diagnosis of gastropleural fistula was made through upper gastrointestinal endoscopy and thoracoabdominal multislice spiral tomography. The treatment was by laparotomy and thoracotomy. Conclusions: Gastropleural fistula due to firearm projectile is an infrequent entity, with multiple diagnosis and surgical treatment. This requires early diagnosis for timely management, which depends on the prognosis of patients. Key words: Thoracic Injury; Gastropleural fistula; Intercostal drainage, Gun injury (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1600